Apparent Insulin Deficiency in an Adult African Population With New-Onset Type 2 Diabetes - Kibirige, Davis; Sekitoleko, Isaac; Balungi, Priscilla; Lumu, William; Nyirenda, Moffat J. (Frontiers in Clinical Diabetes and Healthcare, 2022)
Abstract Identifying patients with new-onset type 2 diabetes who have insulin deficiency can aid in timely insulin replacement therapy. In this study, we measured fasting C-peptide concentration to assess endogenous insulin secretion and determine the prevalence and characteristics of patients with insulin deficiency in adult Ugandan patients with confirmed type 2 diabetes at presentation. Methods Adult patients with new-onset diabetes were recruited from seven tertiary hospitals in Uganda. Participants who were positive for the three islet autoantibodies were excluded. Fasting C-peptide concentrations were measured in 494 adult patients, and insulin deficiency was defined as a fasting C-peptide concentration <0.76 ng/ml. The socio-demographic, clinical, and metabolic characteristics of participants with and without insulin deficiency were compared. Multivariate analysis was performed to identify independent predictors of insulin deficiency. Results The median (IQR) age, glycated haemoglobin (HbA1c), and fasting C-peptide of the participants was 48 (39-58) years,10.4 (7.7-12.5) % or 90 (61-113) mmol/mol, and 1.4 (0.8-2.1) ng/ml, respectively. Insulin deficiency was present in 108 (21.9%) participants. Participants with confirmed insulin deficiency were more likely to be male (53.7% vs 40.4%, p=0.01), and had a lower body mass index or BMI [p<0.001], were less likely to be hypertensive [p=0.03], had reduced levels of triglycerides, uric acid, and leptin concentrations [p<0.001]), but higher HbA1c concentration (p=0.004). On multivariate analysis, BMI (AOR 0.89, 95% CI 0.85-0.94, p<0.001), non-HDLC (AOR 0.77, 95% CI 0.61-0.97, p=0.026), and HbA1c concentrations (AOR 1.08, 95% CI 1.00-1.17, p=0.049) were independent predictors of insulin deficiency. Conclusion Insulin deficiency was prevalent in this population, occurring in about 1 in every 5 patients. Participants with insulin deficiency were more likely to have high HbA1c and fewer markers of adiposity and metabolic syndrome. These features should increase suspicion of insulin deficiency and guide targeted testing and insulin replacement therapy.